COVID-19 Related Terms in Online News Headlines: Critical Discourse Analysis (e-Journal of Linguistics, 2023)
This research aims to construct news headlines related to COVID-19terms in Indonesia. The data source is from various online news mediasuch as health.detiknews.com, kompas.com, and liputan6.com. Datawas collected by only selecting headline news text with istilah (terms)and COVID-19. The data were analyzed using Norman Fairclough’scritical discourse analysis approach. The results showed that throughthe microstructural dimension, the eight news headlines used linguistictools with 1) diction or vocabulary selection focused on the use of theword COVID-19, and 2) grammatical units dominated by phrases, 3)syntactic functions dominated by descriptions as topicalization ofdiscourse, and 4) the form of news that is emphasized on statementsregarding the change or replacement of various terms related toCOVID-19. Then, through the mesostructural dimension, the threeonline mass media have different characteristics and characters indelivering news, especially related to COVID-19 terms, but still beingpresented accurately and objectively so that news content can beconveyed to readers. Finally, through the macrostructural dimension, itwas revealed that a political system demonstrated the power of thegovernment and the Ministry of Health in determining the use ofvarious COVID-19 terms in Indonesia.
Keywords: COVID-19 terms; terms, critical discourse analysis; news headlines; online news media